Pinecone 1949 - Georgia State Womans College (Georgia State Womans College, 1949)
Reminiscing about 1949 at the Georgia State Womans College, Valdosta. And recalling all that happened between freshman week and graduation.
A yearbook was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; Americana